Find the integral surface passing through the initial data curve C: x0= -1, y0= s, z0= (s)1/2 of the equation (x+2)p +2yq =2z
we have to find the integral surface of the equation :
"(x+2)p+2yq=2z..........(1)"
From observation we can see that it is "Lagrange's partial differential equation" of type
"Pp+Qq=R"
So, from equation"(1)" we get Lagrange's auxiliary equation
"\\frac{dx}{x+2}=\\frac {dy}{2y}=\\frac{dz}{2z}\\,.............(2)"
Now we take
"\\frac{dx}{x+2}=\\frac{dy}{2y}"
"\\implies\\intop\\frac{dx}{x+2}=\\intop\\frac{dy}{2y}\\\\\\implies\\ln(x+2)=\\frac{1}{2}\\ln y+\\ln c_1\\\\\\implies\\ln(x+2)-\\ln(\\sqrt{y})=ln c_1\\\\\\implies\\frac{x+2}{\\sqrt{y}}=c_1............(3)"
we will take another equation
"\\frac{dy}{2y}=\\frac{dz}{2z}\\\\\\implies\\intop\\frac{dz}{2z}=\\intop\\frac{dy}{2y}\\\\\\implies\\frac{1}{2}\\ln z-\\frac{1}{2}ln y=\\ln\\sqrt{c_2}\\\\\\implies\\sqrt{\\frac{z}{y}}=\\sqrt{c_2}\\\\\\implies\\frac{z}{y}=c_2..............(4)"
Now it is given that
"x_0=-1;y_0=s_0;z_0=\\sqrt{s_0}\\\\"
putting the values of "x_0;y_0;z_0" in the equation (3) &(4) we get
"c_1=\\sqrt{\\frac{1}{s_0}}" & "c_2=" "\\sqrt{\\frac{1}{s_0}}"
now putting the values of C1& C2 we get
"\\frac{x+2}{\\sqrt{y}}=\\sqrt{\\frac{1}{s_0}}.......(5)" & "\\frac{z}{y}=\\sqrt{\\frac{1}{s_0}}..........(6)"
now subtracting equation (5) to equation (6) we will get
"\\frac{x+2}{\\sqrt{y}}=" "\\frac{z}{y}"
Hence
"\\frac{x+2}{\\sqrt{y}}=" "\\frac{z}{y}" ; is the equation of the integral surface of the given equation.
Comments
Leave a comment